Toward site-specific, homogeneous and highly stable fluorescent silver nanoclusters fabrication on triplex DNA scaffolds - Feng, Lingyan; Huang, Zhenzhen; Ren, Jinsong; Qu, Xiaogang (Nucleic acids research, 2012)
A new strategy to create site-specific, homogeneous, and bright silver nanoclusters (AgNCs) with high-stability was demonstrated by triplex DNA as template. By reasonable design of DNA sequence, homogeneous Ag(2) cluster was obtained in the predefined position of CG.C(+) site of triplex DNA. This strategy was also explored for controlled alignment of AgNCs on the DNA nanoscaffold. To the best of our knowledge, this was the first example to simultaneously answer the challenges of excellent site-specific nucleation and growth, homogeneity and stability against salt of DNA-templated AgNCs.